Triazine Derivative as Putative Candidate for the Reduction of Hormone-Positive Breast Tumor: In Silico, Pharmacological, and Toxicological Approach - Tayyab Imtiaz, Muhammad; Anwar, Fareeha; Saleem, Uzma; Ahmad, Bashir; Hira, Sundas; Mehmood, Yumna; Bashir, Manal; Najam, Saima; Ismail, Tariq (Frontiers in Pharmacology, 2021)
Background and objectives: Breast cancer is a heterogeneous disease that poses the highest incidence of morbidity among women and presents many treatment challenges. In search of novel breast cancer therapies, several triazine derivatives have been developed for their potential chemotherapeutic activity. This study aims to evaluate the N-nitroso-N-methyl urea (NMU)–induced anti–mammary gland tumor activity of 2,4,6 (O-nitrophenyl amino) 1,3,5-triazine (O-NPAT). Methods: The in silico modeling and in vitro cytotoxicity assay were performed to strengthen the research hypothesis. For in vivo experimentation, 30 female rats were divided into five groups. Group I (normal control) received normal saline. Group II (disease control) received NMU (50 mg/kg). Group III (standard control) was treated with tamoxifen (5 mg/kg). Groups IV and V received O-NPAT at a dose level of 30 and 60 mg/kg, respectively. For tumor induction, 3 intraperitoneal doses of NMU were given at a 3-week interval, whereas all treatment compounds were administered orally for 14 consecutive days. Biochemical and oxidative stress markers were estimated for all experimental animals. DNA strand breakage alongside inflammatory markers was also measured for the analysis of inflammation. The hormonal profile of progesterone and estrogen was also estimated. Results: The test compound presented a significant reduction in organ weight and restored the hepatic and renal enzymes. O-NPAT treatments enhanced the antioxidant enzyme level of catalase (CAT), superoxide dismutase (SOD), and total sulfhydryl (TSH), with a highly significant reduction in lactate dehydrogenase (LDH) and lipid peroxidation. Also, the decrease in fragmented DNA, hormonal levels (estradiol and progesterone), and inflammatory cytokines (IL-6 and TNF-α) justified the dosage efficacy further supported by histopathological findings. Conclusion: All results indicated the anti–breast tumor activity of O-NPAT and presented its possibility of exploitation for beneficial effects in breast cancer treatment.